PREDICTORS OF THE DEVELOPMENT OF POSTOPERATIVE VENTRAL HERNIAS AND THEIR PREVENTION IN URGENT SURGERY - A. V. Fedoseev; A. S. Inyutin; S. N. Lebedev; V. S. Shklyar (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
The problem of predicting and preventing postoperative ventral hernias is highly relevant. We examined 450 patients to identify predictors of hernia formation and determine its risk. Seventy-one patients have undergone MRI of the anterior abdominal wall to assess its morphology. We have identified minor and major predictors of hernia formation. Changes in the anterior abdominal wall tissues significant for the pathogenesis of herniation detected during MRI, prevailed in the elderly patients, especially aponeurosis defects that cannot be detected by physical examination, which implies a high risk of postoperative ventral hernias. We used methods of surgical prevention with the consideration of the risk of postoperative ventral hernias. Laparorrhaphy with the staggered strengthening suture is recommended for low-risk patients, whereas high-risk patients should undergo preventive grafting or laparorrhaphy using a polypropylene mesh implant according to the developed technique (if grafting is impossible).